Administrative and ethno-linguistic boundaries of Western Tigray (Ethiopia) since 1683 - Jan Nyssen; Biadgilgn Demissie (Journal of Maps, 2023)
ABSTRACTThe geographical configuration of northwest Ethiopia has changed often and significantly during the previous four centuries, according to a meta-analysis of historical maps. Boundary lines of languages in use and of territorial control were reported on the Main Map. Sixty-six coeval historical maps depict the territorial control of Western Tigray, also known as Welkait and its surrounding districts. The area is specifically recorded as part of Tigray from 1707 to 1794, 1831 to 1886, and 1939 to 1941. From 1891 to 1909 and 1944 to 1990, it is labelled as being a part of Amhara or Gondar. Welkait is shown in other eras as either being autonomous or a component of a broader Mezaga lowland territory. The agreement of 32 ethnolinguistic maps of northern Ethiopia from the twentieth century sustains the post-1991 extent of the Tigray region in the districts located between the Tekeze River and the Sudanese border.